A Stereoscopic Perspective on the Triple-Phase Interface Microenvironment in Electrochemical CO2 Reduction: Insights from In Situ Studies - Zhang, Guiru; Shen, Peng; Li, Xiangrui; Zhu, Lei; Shen, Shuiyun; Zhang, Junliang; Huang, Zhen (Nano-Micro Letters, 2026)
When powered by renewable electricity, the electrochemical carbon dioxide reduction reaction (CO2RR) represents a transformative strategy for achieving sustainable carbon–neutral cycles. Researchers are striving to decode its ambiguous mechanisms through in situ characterization and establish structure–activity correlations in CO2RR systems under operating conditions. Despite these efforts, building a coherent framework that connects insights into atomic-level processes to macroscopic system behavior remains challenging. From this perspective, we present a holistic overview of the critical microregions in CO2RR systems and the associated phenomena requiring scrutiny at the triple-phase interface from a stereoscopic perspective. We systematically summarize recent advances in in situ characterization techniques applied across the distinct microregions, including the electrolyte microenvironment, reaction interface, electrocatalyst structure, and diffusion field. By integrating these insights, we highlight advances in mapping the dynamic cross-compartment interactions and transient species formation mechanisms within the CO2RR process. Finally, we conclude with suggestions for future research, emphasizing the need for synergistic integration of in situ characterization tools and innovative methodologies to resolve lingering mechanistic ambiguities. Such advancements could accelerate the rational design of efficient CO2RR systems and development of sustainable energy solutions. Highlights: 1 The recognition and characterization methods of each microregion at the typical triple-phase interface of carbon dioxide reduction reaction are summarized and elucidated to enhance the understanding of the complex methodologies for interfacial observation and the underlying reaction mechanisms. 2 The key species characteristics, electrochemical reaction mechanisms, and core interactions of different microregions are systematically summarized. 3 Preliminary explorations of multiple synergistic characterization approaches and potential future in situ characterization strategies are pointed out.